Perkembangan Pola Komunikasi dalam Penyuluhan Pertanian di Indonesia - Dwi Sadono (Jurnal Komunikasi Pembangunan, 2009)
Communication model in agricultural extention practices in Indonesia have develoved parallel by the developmentconcept of communication and community. This paper describe several models which dominant used in Indonsia, thatis: 1) One way model, 2) two way hierarkhis model, 3) media forum model, 4) networking model, and 5)eksperimental learning cycle model.